2011
DOI: 10.1089/cyber.2009.0256
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Flow Experience in Web-Based and Text-Based Interaction Environments

Abstract: The purpose of this study was to explore a substantial phenomenon related to flow experiences (immersion) in text-based interaction systems. Most previous research emphasizes the effects of challenge/skill, focused attention, telepresence, web characteristics, and systems' interface design on users' flow experiences in online environments. However, text-based interaction systems without telepresence features and web characteristics still seem to create opportunities for flow experience. To explore this phenome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 32 publications
(60 reference statements)
0
17
0
Order By: Relevance
“…Certain, as yet uncovered, facets of gaming experiences may be more crucial to determining a video game player's tendencies to become addicted to a certain game or in getting into a state of flow while playing it. Rather, it is possible that other factors may more crucial to getting into a flow state when gaming, such as the speed with which the gamer can interact with the gaming environment or the need for a focused attentional state (Huang, Chiu, Sung & Farn, 2011). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain, as yet uncovered, facets of gaming experiences may be more crucial to determining a video game player's tendencies to become addicted to a certain game or in getting into a state of flow while playing it. Rather, it is possible that other factors may more crucial to getting into a flow state when gaming, such as the speed with which the gamer can interact with the gaming environment or the need for a focused attentional state (Huang, Chiu, Sung & Farn, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…This taxonomy was based on the seminal work by Wood, Griffiths, Chappell and Davies (2004) who identified inherent characteristics of a video game that were structural and likely to induce initial gaming activities or maintenance of gaming, irrespective of any other differentiating factor such as the socioeconomic status, age, sex, and so forth. There has also been preliminary recent evidence (King, Delfabbro & Griffiths, 2011) to demonstrate that some structural features inherent in certain games are particularly associated with problematic behaviour that could pose a risk to players of having increased video game addiction tendencies. For example, King, Delfabbro and Griffiths (2011) found that video game players who were exhibiting problematic tendencies were more likely than so-called ‘normal’ players to look to games that provided increasing rewards in the game (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Internal dimensions of the subjective experience such as the autonomy (wanting to do the experience), the balance of high challenges and high skills, the importance of the activity, the perception of success at the activity and focused attention explained 45% of the variation in flow in adolescents' daily life . Huang, Chiu, Sung, and Farn (2011) also found that focused attention was a critical determinant of the immersion dimension of flow, but, specifically, in web-based and text-based interaction environments. In a recent qualitative study of Choe et al (2015), adolescents (16 to 18 years) identified the sense of control as the psychological condition that facilitates students' flow in learning.…”
Section: Flow Experience In Adolescencementioning
confidence: 91%
“…In a cyclic fashion, the more flow a gamer experiences, the stronger the sense of immersion into virtual reality. Though immersion and flow can be disentangled, they are conceptually and empirically related (Faiola, Newlon, Pfaff, & Smyslova, 2013); many authors simply equate the two (see also Huang, Chiu, Sung, & Farn, 2011). Also the scale we used (see Methods) refers to telepresence and immersive aspects of flow; hence for the present purpose we will use the terms ''flow'' and ''immersion'' interchangeably.…”
Section: Involvement Identification and Realism In Computer Gamingmentioning
confidence: 99%